1998
DOI: 10.1073/pnas.95.8.4164
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of cellular translational control by a viral truncated eukaryotic translation initiation factor 2α kinase homolog

Abstract: Phosphorylation of eukaryotic translation initiation factor 2␣ (eIF2␣) is a common cellular mechanism to limit protein synthesis in stress conditions. Baculovirus PK2, which resembles the C-terminal half of a protein kinase domain, was found to inhibit both human and yeast eIF2␣ kinases. Insect cells infected with wild-type, but not pk2-deleted, baculovirus exhibited reduced eIF2␣ phosphorylation and increased translational activity. The negative regulatory effect of human protein kinase RNA-regulated (PKR), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
50
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(56 citation statements)
references
References 42 publications
6
50
0
Order By: Relevance
“…For example, poliovirus infection results in the degradation of PKR (6,7). Several viruses block activation of PKR by sequestering dsRNA or by interfering with PKR dimerization or enzymatic activity (26,27,32,64,65,72). The herpes simplex virus ␥34.5 gene product blocks the effects of PKR by cooperating with cellular protein phosphatase 1␣ to dephosphorylate eIF2␣-phosphate (37).…”
Section: Discussionmentioning
confidence: 99%
“…For example, poliovirus infection results in the degradation of PKR (6,7). Several viruses block activation of PKR by sequestering dsRNA or by interfering with PKR dimerization or enzymatic activity (26,27,32,64,65,72). The herpes simplex virus ␥34.5 gene product blocks the effects of PKR by cooperating with cellular protein phosphatase 1␣ to dephosphorylate eIF2␣-phosphate (37).…”
Section: Discussionmentioning
confidence: 99%
“…Because subsequent structural studies (7,8,21) revealed that dimerization-dependent activation of eIF2α kinases is the exclusive function of the kinase N-lobe, whereas substrate recognition is mediated by helix αG in the kinase C-lobe, one would reasonably predict that PK2 might function by competitively sequestering eIF2α. Surprisingly, however, PK2 coimmunoprecipitated with PKR when coexpressed in yeast and also inhibited PKR KD autophosphorylation (20). Further suggesting that PKR, and not eIF2α, was the interaction target of PK2, a yeast slow-growth phenotype caused by PK2 overexpression was rescued by overexpression of a catalytically inactive PKR K296R but not by eIF2α (20).…”
Section: Significancementioning
confidence: 81%
“…When PKR was overexpressed in baculovirus-infected caterpillar moth cell lines, viral PK2 reduced eIF2α phosphorylation and stimulated virus replication (20). In addition, when PKR was expressed in yeast, PK2 alleviated PKR-mediated translational arrest and toxicity by preventing phosphorylation of yeast eIF2α.…”
Section: Significancementioning
confidence: 99%
See 2 more Smart Citations